Avaliação da qualidade de vida de pacientes com desordens temporomandibulares submetidos à cirurgia articular - Zanin, Roberto Ferreira (2017)
Temporomandibular disorders (TMD) and their treatment have a physical and psychological impact on quality of life (QOL). This study aimed to assess the impact of oral health on QOL by evaluating 50 patients with bilateral anterior disc displacement without reduction preoperatively (T0) and 3–6 months after surgery for anterior disc repositioning and anchoring (T1). Oral health-related QOL was assessed using the short form of the Oral Health Impact Profile (OHIP-14). There was a statistically significant reduction in the mean total OHIP-14 score between T0 (12.48 ± 5.81) and T1 (3.84 ± 3.00). In addition, there was a significant decrease in all 7 OHIP-14 domains (P<0.001). Younger patients (aged 28–38 years, n=26) had benefits in all domains, while older patients (aged 50–60 years, n=5) showed a significant improvement only in the physical pain domain (P=0.049). The results suggest that TMD affect individuals in many aspects of their lives and that general or condition-specific oral health-related QOL measures are valuable tools for determining the impact of joint disorders on patients’ QOL. Surgical treatment for articular disc repositioning and anchoring had a positive impact on patients’ QOL.